2003
DOI: 10.1023/a:1025658432696
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A mathematical model (sigma(omega) approximately equal to A omega alpha, where, sigma is identical with conductivity, omega = 2 pi f is identical with applied frequency (Hz), A (amplitude) and alpha (unit less) is identical with search parameters) was used to fit the frequency dependence of electrical conductivities of compact, spongiosum, and bulk layers of the live and, subsequently, dead human skull samples. The results indicate that the fit of this model to the experimental data is excellent. The ranges of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Previous literature has examined skull conductivity in wider frequencies, revealing a positive relationship, especially at frequencies higher than 10 kHz (Gabriel et al 1996b; Tang et al 2008), and suggest skull conductivity may exponentially increase at high frequencies. Within the relevant range for brain activity, skull conductivity increased by ~ 6.7% from 11 to 127 Hz (Dabek et al 2016) and ~ 13% from 10 to 90 Hz (Akhtari et al 2002), of which the authors developed a non-linear model for frequency dependence of different skull layers (Akhtari et al 2003). Variation as a function of frequency may be expected due to interactions between mobile electrolytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has examined skull conductivity in wider frequencies, revealing a positive relationship, especially at frequencies higher than 10 kHz (Gabriel et al 1996b; Tang et al 2008), and suggest skull conductivity may exponentially increase at high frequencies. Within the relevant range for brain activity, skull conductivity increased by ~ 6.7% from 11 to 127 Hz (Dabek et al 2016) and ~ 13% from 10 to 90 Hz (Akhtari et al 2002), of which the authors developed a non-linear model for frequency dependence of different skull layers (Akhtari et al 2003). Variation as a function of frequency may be expected due to interactions between mobile electrolytes (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Each set of data was obtained at current amplitude of 60 μA. The overall errors in potential and phase measurements were determined by replacing the sample with a known resistor (R = 988 Ω) and a R||C circuit respectively (Akhtari et al 2003).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Computer simulations of the current flow during tDCS using human head models have revealed that a significant amount of the current is shunted by the well-conducting skin (~90%), while much less of the current actually reaches the brain [ 22 ]. In the case of tACS, the different frequency response of each type of conducting element between the electrodes and the brain should also be taken into account [ 23 ].…”
Section: How Can Tacs Influence Cortical Activity?mentioning
confidence: 99%